The Impact of Human Critical Success Factor on ERP System Implementation - Fasti Herianty Akhzan; Grace T Pontoh; Arifuddin Arifuddin (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
Many researchers have investigated the critical success factors in ERP system implementation. The previous study has examined four primary human critical success factors (competence, behavior, team composition, and communication) and based on study literature performed by the author, there were many studies found that top management support also has crucial role in ERP implementation. The objective of this study is to examine the impact of top management support, competence, behavior, team composition, and communication in ERP implementation.This study was conducted in three stages. First, review sources and scientific literature relevant to this research. Second, analyze the findings and recommendations of previous research to determine the component of variable x. Third, conduct research using a quantitative approach through a questionnaire survey. Questionnaires were distributed to employees from various company that involved directly in ERP implementation. This study found that all five variables positively correlated to project success and only team composition variable that significantly positively correlated to project success. This study offers ERP project managers the crucial factors needed to be concerned for the project success.Keywords: ERP, Human Critical Success Factors.